2017
DOI: 10.1080/21691401.2017.1296849
|View full text |Cite
|
Sign up to set email alerts
|

Cardamom fruits as a green resource for facile synthesis of gold and silver nanoparticles and their biological applications

Abstract: Gold (FA-AuNps) and silver (FA-AgNps) nanoparticles were synthesized at room temperature by aqueous extract of dried fruits of Amomum villosum, also known as Fructus Amomi (cardamom), in order to confer antioxidant, catalytic, antimicrobial activities and treatment effect against breast cancer cells. Fruit extracts served as both reducing agents and stabilizers in lieu of chemical agents. Ultra-violet visible (UV-Vis) spectroscopy, field emission transmission electron microscopy (FE-TEM), energy-dispersive X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(56 citation statements)
references
References 28 publications
9
42
0
Order By: Relevance
“…No zone formation (Table 3) for both strains in case of AgNO 3 salt solution exhibits their resistance. BSNPs surpassed the antibiotics tested consistent with biogenic AgNPs expressing potent antimicrobial activity towards different antibiotics [18]. Moreover, pronounced augmentation in ZOI was observed with an increase in BSNPs conc.…”
Section: Resultssupporting
confidence: 66%
“…No zone formation (Table 3) for both strains in case of AgNO 3 salt solution exhibits their resistance. BSNPs surpassed the antibiotics tested consistent with biogenic AgNPs expressing potent antimicrobial activity towards different antibiotics [18]. Moreover, pronounced augmentation in ZOI was observed with an increase in BSNPs conc.…”
Section: Resultssupporting
confidence: 66%
“…When the AgNPs were incubated both in pH 7.4 and pH 5 buffers, it was seen that silver ion release was more at acidic pH, confirming the selective killing of cancer cells at lower pH. It is also confirmed that the formation of nanoparticle aggregation can control the cervical cancer cell and non-aggregates can increase the cellular viscosity and disturb the important cellular processes that eventually leads to cellular apoptosis [32]. Anti-angiogenic properties of AgNPs are also illustrated by some researchers.…”
Section: Mechanism Of Anticancer Activitymentioning
confidence: 67%
“…were reported for good antibacterial activity against pathogenic bacterial strains. Some study also reported that silver nanoparticles show good action against some strains which were resistant to the common antifungal agent Fluconazole [112]. Furthermore, Birla et al [113] reported that silver nanoparticles in combination with commercially available antimicrobial drugs shows higher activity as compare to drug alone.…”
Section: Bio-prospective Applications Of Mycogenic Nanoparticlesmentioning
confidence: 99%